BASANITE GLACIOVOLCANISM AT LLANGORSE MOUNTAIN, NORTHERN BRITISH COLUMBIA, CANADA - Harder M.; Russell Ja.K. (My University, 2007)
The Llangorse volcanic field is located in northwest British Columbia, Canada, and comprises erosional remnants of Miocene to Holocene volcanic edifices, lava flows or dykes. The focus of this study is a single overthickened, 100-m-thick-valley-filling lava flow that is Middle-Pleistocene in age and located immediately south of Llangorse Mountain. The lava flow is basanitic in composition and contains mantle-derived peridotite xenoliths. The lava directly overlies a sequence of poorly sorted, crudely bedded volcaniclastic debris-flow sediments. The debris flow deposits contain a diverse suite of clast types, including angular clasts of basanite lava, blocks of peridotite coated by basanite, and rounded boulders of granodiorite. Many of the basanite clasts have been palagonitized. The presence and abundance of clasts of vesicular to scoriaceous, palagonitized basanite and peridotite suggest that the debris flows are syngenetic to the overlying lava flow and sampled the same volcanic vent during the early stages of eruption. They may represent lahars or outburst floods related to melting of a snow pack or ice cap during the eruption. The debris flows were water-saturated when deposited. The rapid subsequent emplacement of a thick basanite flow over the sediments heated pore fluids to at least 80–100°C causing in-situ palagonitization of glassy basanite clasts within the sediments. The over-thickened nature of the Llangorse Mountain lavas suggests ponding of the lava against a down-stream barrier. The distribution of similar-aged glaciovolcanic features in the cordillera suggests the possibility that the barrier was a lower-elevation, valley-wide ice-sheet.
Keywords: GLACIOVOLCANISM; BASANITE; LAHAR; PALAGONITE; THERMAL-MODEL; BRITISH COLUMBIA; Holocene; Pleistocene; Miocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен